The burden of carbapenem-resistant Enterobacterales infection in a large Thai tertiary care hospital - Tangsawad, Watcharaphon; Kositamongkol, Chayanis; Chongtrakool, Piriyaporn; Phisalprapa, Pochamana; Jitmuang, Anupop (Frontiers in Pharmacology, 2022)
Background: Carbapenem-resistant Enterobacterales (CRE) are resistant to several other classes of antimicrobials, reducing treatment options and increasing mortality. We studied the clinical characteristics and burden of hospitalized adult patients with CRE infections in a setting where treatment options are limited. Methods: A retrospective cohort study included adult inpatients between January 2015–December 2019 at Siriraj Hospital in Bangkok, Thailand. Clinical and microbiological data were reviewed. Results: Of 420 patients with CRE infections, the mean age was 65.00 ± 18.89 years, 192 (45.72%) were male, and 112 (26.90%) were critically ill. Three hundred and eighty (90.48%) had Klebsiella pneumoniae, and 40 (9.52%) had Escherichia coli infections. The mean APACHE II score was 14.27 ± 6.36. Nearly half had previous hospitalizations (48.81%), 41.2% received antimicrobials, and 88.1% had undergone medical procedures before the onset of infection. The median time of onset of CRE infection was 16 days after admission. Common sites of infection were bacteremia (53.90%) and pneumonia (45.47%). Most CRE-infected patients had septic shock (63.10%) and Gram-negative co-infections (62.85%). Colistin (29.95%) and non-colistin (12.91%) monotherapies, and colistin-based (44.78%) and non-colistin-based (12.36%) combination therapies were the best available antimicrobial therapies (BAAT). The median length of hospitalization was 31 days, and the median hospitalization cost was US$10,435. The in-hospital mortality rate was 68.33%. Septic shock [adjusted odds ratio (aOR) 10.73, 5.65–20.42, p <0 .001], coinfection (aOR 2.43, 1.32–4.47, p = 0.004), mechanical ventilation (aOR 2.33, 1.24–4.36, p = 0.009), and a high SOFA score at onset (aOR 1.18, 1.07–1.30, p <0 .001) were associated with mortality. Conclusion: CRE infection increases mortality, hospital stays, and healthcare costs. A colistin-based regimen was the BAAT in this study. Therefore, newer antimicrobial agents are urgently needed.